The Many Masks of Karol Szymanowski: A discussion of his two piano triptychs (Música Hodie, 2012)
This article explores the relationship between Karol Szymanowski's two piano triptychs – Métopes, op. 29, and Masques, op. 34 – and the literary characters evoked by each of their movements – the Sirens, Calypso and Nausicaa (from Homer's Odyssey), Sheherazade (from The Arabian Nights), Tristan (from Hardt's play Tantris le Bouffon), and Don Juan (not associated to any specific source by the author). The article discusses various strategies used by the composer to convey his subject matter, from obvious visual depictions to hidden structural parallelisms, thus demonstrating how he used both the content and the form of the literary narratives as inspiration.Keywords: Szymanowski; Piano; Program music; Literature.